SURVIVAL ABILITY IN SIMULATED GASTROINTESTINAL TRACT OF LACTIC ACID BACTERIA ISOLATED FROM PICKLED CABBAGE - Dangmanee, Nattakan; Hounkong, Kruawan (Interprofessional Journal of Health Sciences, 2023)
The aim of the present study was to examine potential probiotic properties of lactic acid bacteria PK3, PK5 and PK6 isolated from pickled cabbage. Acid (pH 2-4) and bile (0.1-0.3%) tolerance and survival in stimulated gastrointestinal tract of these isolates were evaluated. It was found that lactic acid bacteria PK6 showed good acid and bile tolerance and high survival rate in stimulated gastric fluid and stimulated intestinal fluid to develop it as a potential probiotic candidate.